Unilateral retention of testis in a buck - TANDLE, M K; HONNAPPAGOL, S S (The Indian Journal of Animal Reproduction, 2023)
A rare case of unilateral retention of testis in a buck has been reported in the present paper.
Keywords: Testis retention; buck